PATTERNS OF TEACHERS’ INTERPERSONAL COMMUNICATION IN THE MANAGEMENT OF ISLAMIC CHARACTER BUILDING AT THE INSAN MULIA RABBANI INTEGRATED ISLAMIC ELEMENTARY SCHOOL IN THE TALANG UBI DISTRICT - Ega Rismasita; Ahmad Zainuri; Karoma Karoma; Yulia Tri Samiha (LP2M IAI Al-Khairat Pamekasan, 2026)
This research examines Teacher Interpersonal Communication Patterns in the Management of Islamic Character Development at Insan Mulia Rabbani Integrated Elementary School in Talang Ubi District. The study aims to explore the interpersonal communication methods of educators and the management tactics used in instilling Islamic character, particularly through the core activities of Islamic Personal Development (Bina Pribadi Islami/BPI). Information collection utilized triangulation (in-depth interviews, observation, and document review). Data analysis was conducted inductively and interactively, encompassing data condensation to identify key points, structured presentation of findings, and drawing valid conclusions. The main conclusion indicates that verbal interactions between teachers and students are highly flexible and personal, emphasizing exemplary behavior (uswah hasanah) and adapting the language of advice. Key management tactics include the implementation of graduated sanctions and the alignment of school values ​​with the family environment through the Amal Yaumiyah program. Although the strategy has been implemented, crucial obstacles have emerged, such as the limited time allocated for BPI and minimal parental participation (approximately 20%). Based on these findings, the study suggests improving resources and establishing a more flexible communication approach, aimed at strengthening internal coordination and increasing the active role of external parties for the sustainability of character building.